(untitled) (KYAMC Journal, 2017)
Objective: To compare efficacy and safety of oral misoprostol over vaginal misoprostol for labour induction. Materials and Methods: This is a cross sectional interventional hospital based comparative study which was carried in the department of Obstetrics and Gynecology in DMCH from 01.07.2008 to 31.12.2008. Results: Almost equal number of patients delivered vaginally spontaneously in both group, there is no association between route of administration and mode of delivery. Nausea,vomiting occurred more in oral group and uterine hypertonicity more in vaginal group. Conclusion: In this study, 50 patients were randomly selected for oral group and 50 patients for vaginal group. There were no significant differences regarding age, duration of pregnancy, Bishop’s score and indication of induction of labour. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 668-672